2016
DOI: 10.1111/asj.12572
|View full text |Cite
|
Sign up to set email alerts
|

Use of monosodium glutamate by‐product in cow diet on performance of lactating dairy cows

Abstract: Eight multiparous lactating Holstein cows were randomly assigned in a 4 × 4 replicated Latin square design to receive four dietary treatments. The dietary treatments were monosodium glutamate by-product (MSGB) replacement for soybean meal in concentrate at four levels: MSGB replacement at 0, 20, 40 and 60%, respectively. Pangola hay was given on an ad libitum basis. It was found that total dry matter intake, concentrate intake, pangola hay intake and all apparent digestibilities were not different among treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…Baumont (1996) reported that small ruminants will develop for the taste of monosodium glutamate in the diet. These results agreed with earlier results indicated that added monosodium L-glutamate (1.5 g/kg DM) to the diet of early lactation cows was found no effect on DM intake (Nombekela et al 1994) and Padunglerk et al (2017) demonstrated that feed composed of monosodium glutamate by-product 10-15% did not affect feed intake and nutrient digestibilities in dairy cows. Due to the glutamic acid contained in animal feed might stimulate animal feed intake, gastric emptying, stimulation of saliva, gastric and pancreatic juices secretion, growth of visceral organs and trophic action in faster growing tissues as reported by Halpern (2000); Lackeyram et al (2001); Mateo (2005) and Toyomasu et al (2010).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Baumont (1996) reported that small ruminants will develop for the taste of monosodium glutamate in the diet. These results agreed with earlier results indicated that added monosodium L-glutamate (1.5 g/kg DM) to the diet of early lactation cows was found no effect on DM intake (Nombekela et al 1994) and Padunglerk et al (2017) demonstrated that feed composed of monosodium glutamate by-product 10-15% did not affect feed intake and nutrient digestibilities in dairy cows. Due to the glutamic acid contained in animal feed might stimulate animal feed intake, gastric emptying, stimulation of saliva, gastric and pancreatic juices secretion, growth of visceral organs and trophic action in faster growing tissues as reported by Halpern (2000); Lackeyram et al (2001); Mateo (2005) and Toyomasu et al (2010).…”
Section: Resultssupporting
confidence: 92%
“…Utilization of industrial by-products for livestock feed is urgently required to raise the international competitiveness of livestock production. Use of MSG by-product (MSGB) in animal feeding has been studied in various animals, addition of MSG in swine diets on carcass quality (Kananurak et al 1987), in cattle on feed intake, growth rate and carcass quality Keaokliang et al (2012) and by Padunglerk et al (2017) in dairy cows, all these studies reported use of MSGB replacement of protein source in non-ruminant and nonprotein nitrogen source in ruminant animals feeding.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the chemical compositions of two types of MLs varied considerably due to the different ingredients. Moreover, the MLs have different chemical compositions from monosodium glutamate by‐product used in a previous study (Padunglerk et al., ). For example, monosodium glutamate by‐product used in the previous study (Padunglerk et al., ) contained more DM (63.3%) and less CP concentrations (46.0% on a DM basis) than these of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although ML mainly has been used as silage additives (Yimiti et al., ) and fertilizer (Yoshimura, ), the liquor has a potential to be utilized for a nitrogen source in animal diets. Only a few experiments, however, have been conducted to investigate the possibility of monosodium glutamate by‐product as a feed for ruminant (Keaokliang, Siwichai, Kongmun, & Prasanpanich, ; Padunglerk, Prasanpanich, & Kongmun, ). Keaokliang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation